2017
DOI: 10.1186/s12879-017-2815-9
|View full text |Cite
|
Sign up to set email alerts
|

Varicella zoster virus-associated morbidity and mortality in Africa – a systematic review

Abstract: BackgroundVaricella zoster virus (VZV) causes varicella and herpes zoster. These vaccine preventable diseases are common globally. Most available data on VZV epidemiology are from industrialised temperate countries and cannot be used to guide decisions on the immunization policy against VZV in Africa. This systematic review aims to review the published data on VZV morbidity and mortality in Africa.MethodsAll published studies conducted in Africa from 1974 to 2015 were eligible. Eligible studies must have repor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
22
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 42 publications
(59 reference statements)
2
22
1
1
Order By: Relevance
“…A literature review of papers published on varicella in Africa between 1974 and 2015 found only 20 articles from 13 countries (24% of the countries in Africa) . Though we were able to collect data on varicella through this monkeypox surveillance platform, distinguishing between varicella and monkeypox in areas where both diseases are endemic—such as in DRC—can be challenging.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…A literature review of papers published on varicella in Africa between 1974 and 2015 found only 20 articles from 13 countries (24% of the countries in Africa) . Though we were able to collect data on varicella through this monkeypox surveillance platform, distinguishing between varicella and monkeypox in areas where both diseases are endemic—such as in DRC—can be challenging.…”
Section: Discussionmentioning
confidence: 98%
“…Few data are available on varicella epidemiology in Africa and most are limited to specific sub-populations, such as HIV-positive populations or refugees [8][9][10][11][12][13][14][15][16]. Varicella epidemiology in temperate climates usually differs from that in tropical climates; in temperate climates most children are infected by 10 years of age while children in tropical climates acquire varicella at older ages and a higher proportion of young adults remain susceptible [17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…1 Herpes zoster (HZ) is characterized by painful vesicular rash with dermatomal distribution. 2 Although it causes many complications, to our knowledge, PMR secondary to HZ has not been previously reported.…”
mentioning
confidence: 78%
“…Indeed, the seroprevalence of HSV1, HSV2, and CMV are estimated to be 87%, 31%, and 82%, respectively [5][6][7][8]. The seroprevalence of VZV is variable across countries and studies in Africa (0-90%) [9]. Few data exist on the prevalence of HHV-6, but it can reach 100% in many regions of the world [10].…”
Section: Introductionmentioning
confidence: 99%